Higher frequencies of circulating ICOS+, IL-21+ T follicular helper cells and plasma cells in patients with new-onset membranous nephropathy. (17th November 2017) - Zhang, Zhihui; Shi, Yunpeng; Yang, Kunmeng; Crew, Rebecca; Wang, Haifeng; Jiang, Yanfang
Abstract: Background: T follicular helper (TFH) cells and B cells are known to regulate humoral immune responses. This study is aimed at examining the putative contribution of different subsets of circulating of TFH cells and B cells to membranous nephropathy (MN). Methods: A total of 45 MN patients and 19 healthy controls (HCs) were examined for the number of TFH cells and B cells by flow cytometry. The level of 24-h urinary protein and eGFR were calculated, and the level of serum cytokines was examined. The potential association among these measures was analyzed. Results: Compared to the HCs, MN patients had significantly higher numbers of circulating CD4 + CXCR5 +, CD4 + CXCR5 + ICOS +, CD4 + CXCR5 + CD154 +, CD4 + CXCR5 + IL-21 +, and CD4 + CXCR5 + CD28 + TFH cells, as well as IgD + CD27 − CD19 + and CD138 + CD19 + B cells. However, the number of IgD + CD27 + CD19 + B cells was significantly lower in MN patients than in the HC. The levels of serum IL-21, IL-2, IL-4, IL-10, IL-17A, and IFN-γ were significantly higher in MN patients than in the HC. Furthermore, the numbers of CD4 + CXCR5 +, CD4 + CXCR5 + ICOS +, CD4 + CXCR5 + CD154 +, CD4 + CXCR5 + IL-21 +, CD4 + CXCR5 + CD28 + TFH cells, CD138 + CD19 + B cells, and the level of sera IL-21 were negatively correlated with the values of eGFR, but positively correlated with the levels of 24-h urinary proteins. Following treatment, the numbers of CD4 + CXCR5 +, CD4 + CXCR5 + ICOS +, CD4 + CXCR5 + CD154 +, CD4 + CXCR5 + IL-21 +, CD4 + CXCR5 + CD28 + TFH cells, CD138 + CD19 + B cells, and the levels of IL-21 were significantly reduced. In contrast, IL-4 and IL-10 levels were noticeably increased after treatment. Conclusions: Data suggest that activated TFH and plasma cells may contribute to the pathogenesis of MN.